2021
DOI: 10.3390/ijerph18116020
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Water Insecurity in Rural Zimbabwe: Development of Multidimensional Household Measures

Abstract: Background: With millions of people experiencing malnutrition and inadequate water access, FI and WI remain topics of vital importance to global health. Existing unidimensional FI and WI metrics do not all capture similar multidimensional aspects, thus restricting our ability to assess and address food- and water-related issues. Methods: Using the Sanitation, Hygiene and Infant Nutrition Efficacy (SHINE) trial data, our study conceptualizes household FI (N = 3551) and WI (N = 3311) separately in a way that cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
(124 reference statements)
0
10
0
Order By: Relevance
“… 59 SHINE women reported collecting water less frequently, the longer the time required to fetch water. 64 Subnational panel data in 59 countries showed that only water piped directly into the home predicted reductions in stunting (β=−0.142; p<0.01), 41 but not other water sources whether piped off-plot or ground. This may be an indication of the ease of water access.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 59 SHINE women reported collecting water less frequently, the longer the time required to fetch water. 64 Subnational panel data in 59 countries showed that only water piped directly into the home predicted reductions in stunting (β=−0.142; p<0.01), 41 but not other water sources whether piped off-plot or ground. This may be an indication of the ease of water access.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, availability, quality, access and household shocks are likely to be affected during the lean season. 64 FI during that time is particularly severe for the rural farming communities. This is because the lean period represents low employment opportunities in agriculture and the dwindling of staple food reserves for the household.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Multidimensional Household Food Insecurity (MHFI) and the Multidimensional Household Water Insecurity (MHWI) measures were used as primary FI and WI exposures, respectively [46]. These measures were developed specifically for the rural Zimbabwean households and their validities were tested to ensure robustness and usefulness.…”
Section: Fi and Wi Exposure Variablesmentioning
confidence: 99%
“…Many efforts have been made to develop various indicators, methods, and options for quantitative assessment of water stress in the current conditions and its future changes at the regional and national levels (Sullivan et al 2006). Water resources-related indicators contribute to water adequacy, help ensure food safety and population needs, and are helpful tools for policymakers in water resources management (Koyratty et al 2021;Ladi et al 2021;Mishra et al 2021).…”
Section: Introductionmentioning
confidence: 99%